Profit Growth, Liquidity, and Profibility on Profit Quality - Alfiandi, Abi; Hendayana, Yayan (Dinasti Publisher, 2024)
Profit quality is very important information related to the company's financial health. The research aims to assess and describe the effect of profit growth, liquidity and profitability on profit quality. Research includes quantitative research. Research materials using food and beverage manufacturing companies on the Indonesia Stock Exchange for the 2019-2021 period. The sample used 19 companies. Multiple linear regression is a technique used in data analysis. The results prove that profit growth and liquidity do not affect profit quality, while profitability affects profit quality. This research is used as a helper for entities and external parties in order to determine the quality of profit in an entity.